Persistent eosinophilia and associated organ involvement in Thai patients with systemic sclerosis: Data from the Siriraj scleroderma cohort - Somsak Punjasamanvong,; Chayawee Muangchan, (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the prevalence of persistent eosinophilia and associated organ complications in Thai patients with systemic sclerosis (SSc). Patients and methods: This post-hoc study included 107 adult patients (23 males, 84 females; mean age: 50.4±11.6 years; range, 18 to 79 years) diagnosed with SSc between November 2013 and June 2017. Eosinophilia was defined as an absolute eosinophil count of >500/μL or a percentage count of >7%. Eosinophil levels collected at every visit over one year were categorized as persistently high (PH), persistently low (PL), high-to-low (HL), low-to-high (LH), or variable levels (VL). The study compared variables between PH and non-PH (PL+HL+LH+VL) groups. The patients with baseline eosinophilia were also identified and compared with the non-eosinophilia group. Results: The median disease duration was 3.2 years. Of the patients, 79.4% had diffuse cutaneous SSc and 76.7% had anti-Scl-70 positivity. A total of 11.2%, 66.4%, 1.9%, 8.4%, and 12.1% of the patients were categorized into the PH, PL, HL, LH, and VL groups, respectively. Compared to non-PH groups, the PH group had a higher prevalence of anti-centromere antibody (ACA), higher baseline percent predicted total lung capacity, and lower baseline C-reactive protein and creatine phosphokinase (p<0.05 for all). The ACA positivity (odds ratio [OR]: 18.5; 95% confidence interval [CI]: 1.64-208.46) was associated with PH. The patients with baseline eosinophilia (17.8%) had a higher prevalence of non-specific interstitial pneumonia with periodic eosinophilia at the time of diagnosis (100% vs. 6.5%, p<0.0001; OR: 4.667; 95% CI: 1.712-12.724). Conclusion: The PH was seldom (11%) in patients with SSc compared to periodic eosinophilia, which was more prevalent (18%). It may be related to ACA positivity and better pulmonary outcomes, whereas periodic eosinophilia may involve interstitial lung disease.